2017
DOI: 10.1101/136226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ketogenic diet or BHB improves epileptiform spikes, memory, survival in Alzheimer’s model

Abstract: The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/136226 doi: bioRxiv preprint first posted online May. 9, 2017; 3 hAPPJ20 (APP) mice carry a human APP transgene with the Swedish and Indiana 1 familial AD-causing mutations (J20 line) 10 and display amyloid deposition, cognitive 2 deficits, spontaneous epileptiform spikes, and high early mortality 5,11 . In order to test if a 3 ketogenic diet would suppress epileptiform spikes in hAPPJ20 mice, we designed a pair 4 of diets matc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The synthesis method for the hexanoyl hexyl b-hydroxybutyrate (C6x2-bHB) ester was developed by Scott Ulrich of Ithaca College (Ithaca, New York, USA) as previously described (Newman et al, 2017b), and the ester was then custom ordered in bulk from AK Scientific (Union City, CA). The bHB moiety of the ester is chiral, and the compound was synthesized as an enantiomeric mixture.…”
Section: Ketone Ester Synthesismentioning
confidence: 99%
“…The synthesis method for the hexanoyl hexyl b-hydroxybutyrate (C6x2-bHB) ester was developed by Scott Ulrich of Ithaca College (Ithaca, New York, USA) as previously described (Newman et al, 2017b), and the ester was then custom ordered in bulk from AK Scientific (Union City, CA). The bHB moiety of the ester is chiral, and the compound was synthesized as an enantiomeric mixture.…”
Section: Ketone Ester Synthesismentioning
confidence: 99%
“…Categories 1 through 6 shown below, along with Figures 1 – 4 , are “ketone esters”, or compounds used to synthesize ketone esters, which are independently capable of elevating circulating ketone bodies-those compounds being 1,3-butanediol and mid-chain carboxylic acids and alcohols. Six ketone esters cover the bulk of studies performed to date, those coming from the Brunengraber group, category 3A.ii ( Desrouchers et al, 1995 ), the Veech/Clarke groups, category 3A.i ( Clarke et al, 2012 ), the Hashim group, category 4A.i ( Hashim, 2014 ) and the Buck Institute, categories 2C.iii.2 and 3B.iii ( Newman et al, 2017 ), ( Stubbs et al, 2021 ) along with medium chain triglycerides, category 4A.ii. Immediately obvious from the structures shown in Figures 1 – 4 are the additional number of compounds possible.…”
Section: Introductionmentioning
confidence: 99%
“…A non-obesogenic ketogenic diet extends lifespan in mouse models and improves healthspan outcomes, including memory, in aged mice [28][29][30] . Additionally, ketogenic diet and exogenous ketones have been shown to improve cognitive and motor behavior in several mouse models of AD [31][32][33][34] . Early human studies of ketogenic compounds have improved cognitive scores in patients with mild to moderate AD [35][36][37][38][39][40] .…”
mentioning
confidence: 99%
“…This work identifies bHB as a global regulator of cytosolic protein solubility, and identifies new metabolism-related mechanistic targets for therapeutic development in aging and AD. RESULTS b-hydroxybutyrate directly induces protein insolubility without posttranslational modification We, and other laboratories, have shown that memory phenotypes in aged mice and mouse models of Alzheimer disease (AD) can be improved with ketogenic therapies [28][29][30][31][32] . While the substrate provision for brain energy metabolism is likely indirectly assisting with these improvements, no direct mechanism has been validated.…”
mentioning
confidence: 99%